Construction of Thienopyrroles through Rhodium-Catalyzed Direct Annulation of (Acetylamino)thiophenes with Alkynes - Hayashi, Mikishiro; Michikita, Ryudai; Usuki, Yoshinosuke; Satoh, Tetsuya (Synthesis, 2023)
The direct annulative coupling of 3-(acetylamino)thiophenes with internal alkynes proceeds smoothly under rhodium catalysis through acetylamino-directed C–H bond cleavage at the C2-position, leading to the effective construction of 4-acetylthieno[3,2-b]pyrrole derivatives. The acetyl directing group on the annulation product is readily removed to produce the 4-unprotected thieno[3,2-b]pyrrole derivative.
Keywords: annulation; C–H functionalization; fused heterocycles; rhodium catalysis; thienopyrrole